Resilience and protection schemes in isolated microgrids - Valencia, Felipe (2015)
This document addresses the concepts of resilience and protection schemes in isolated microgrids. Resilience is defined by the Stockholm Resilience Centre as the capacity of a system to change and adapt continuously without crossing critical thresholds. The study focuses on the Huatacondo microgrid, analyzing its resilience capacity through indicators such as frequency and voltage deviation, photovoltaic installation plant factor, and diesel consumption. Three stages of resilience are evaluated: avoid, withstand, and recover, using a resilience management framework. Results show that the use of adaptive model-based protection schemes improves the coordination of protection devices and captures the peculiarities of isolated microgrids, increasing their ability to absorb and recover from system failures. The research highlights the importance of adequate protection to maintain the critical functionality of microgrids and enhance their resilience to disturbances.